Safety of Unilateral Endovascular Occlusion of the Cervical Segment of the Vertebral Artery without Antecedent Balloon Test Occlusion - Zoarski, G.H. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Antecedent balloon test occlusion is often performed prior to vertebral artery sacrifice, but there is limited data to suggest this adds a significant clinical benefit, especially in the setting of trauma. Furthermore, balloon test occlusion can be time-consuming, add to the technical complexity of the procedure, and increase the overall cost of treatment. The purpose of this study was to determine the safety of unilateral vertebral artery occlusion without antecedent balloon test occlusion as part of the treatment regimen in patients with traumatic vertebral artery dissection, cervical tumor, or intracranial aneurysm. MATERIALS AND METHODS: The medical records and imaging studies of 59 patients in whom unilateral endovascular cervical vertebral artery occlusion was performed were retrospectively reviewed. Procedure-related stroke was defined as imaging evidence of acute infarct in the vascular territories supplied by the occluded vertebral artery or new focal neurologic deficit developing in the first 30 days after vertebral artery occlusion attributable to infarction in the posterior circulation. RESULTS: Fifty-nine patients underwent unilateral endovascular cervical vertebral artery occlusion to prevent potential thromboembolic complications of vertebral artery injury, for treatment of intracranial aneurysms, or for presurgical embolization of a cervical vertebral tumor. Unilateral occlusion was performed when endovascular reconstruction was considered impossible or deemed more risky than deconstruction. Fifty-eight of the 59 patients underwent vertebral artery occlusion without antecedent balloon test occlusion. None of the 59 patients had clinical or imaging evidence of a postprocedural infarct. CONCLUSIONS: In this series, endovascular occlusion of a cervical segment of 1 vertebral artery was safely performed without antecedent balloon test occlusion. As long as both vertebral arteries were patent and converged at the vertebrobasilar junction, there was anatomic potential for retrograde filling of the distal intracranial vertebral artery to the level of the posterior inferior cerebellar artery origin, and there was no major vascular supply to the spinal cord arising from the target segment of the affected vessel. Dominant and nondominant vertebral arteries were safely occluded, and no infarcts were attributed to the treatment.